PERAN CITRA MEREK DAN PENGARUHNYA TERHADAP EKUITAS MEREK HANDPHONE SAMSUNG - Dinan Dinan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This research has background the phenomena of brand competition of various companies in obtaining Top Brand Award. Customers tend to give more trust at any brands that have once achieved the Top Brand Award. Decreased top brand index indicates problems on brand equity of the Handphone Samsung. The problem in this research is “What is Brand Image and Brand Awareness effect on Brand Equity of Samsung Handphone”. Brand image and brand awareness are assumed to have effects on brand equity and greatly importance to build strong brand equity. Therefore, this research aims to analyze the effects of Brand Image and Brand Awareness on Brand Equity of Samsung Handphone.This research used 10 respondents as the samples who have purchased Samsung Handphone with purposive sample and accidental samples. Then, there was data analysis both quantitatively and qualitatively. The qualitative analysis is the interpretation of data that were obtained in the field and open answer analysis given by the respondents, while quantitative analysis includes: reliability test, validity test, classical assumption test, multiple linear regression analysis, F test, t test and determination coefficient analysis (X).Results of this research indicate that brand image (X1) and brand awareness (X2) are proven to significantly affect the brand equity (Y). Out of two analyzed independent variables, the brand awareness is the variables with the biggest effects on the dependent variable, which then is followed by the brand image. Keywords: Brand Image, Brand Awareness, and Brand Equity